2009
DOI: 10.1007/s10641-009-9483-6
|View full text |Cite
|
Sign up to set email alerts
|

Habitat and relative abundance of fishes in small rivers in eastern Thailand

Abstract: Total relative abundance of fish and species richness at 95 sites in small rivers varied significantly with physicochemical factors. Species richness was negatively and positively related with pH and dissolved oxygen, respectively. Relative abundance varied inversely with discharge and ambient ammonia and, directly with depth, substratum, ambient oxygen and alkalinity. Fish were represented by 62 species, the most common being Rasbora paviei, Puntius binotatus and Channa gachua. Canonical correspondence analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 25 publications
1
31
0
Order By: Relevance
“…In our study, as shown by the CCA biplot (comparison of arrow length, ter Braak and Smilauer 2002) the most important environmental variables for the fish assemblage in River Ken were water flow, depth, temperature, turbidity, Total Dissolved Solids, conductivity and land uses. Comparable results are known from investigations on assemblage of other rivers as well (Copp et al 1994;Garner 1996;Sarkar and Bain 2007;Fischer and Paukert 2008;Tongnunui et al 2009;Wu et al 2011), where the respective authors have emphasized the importance of those environmental variables influencing the fish assemblage pattern. Fish preferences of different stream of specific depths have been discussed in literature many times (Pires et al 1999) and likewise to the speed of flow (Penczak et al 2004).…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…In our study, as shown by the CCA biplot (comparison of arrow length, ter Braak and Smilauer 2002) the most important environmental variables for the fish assemblage in River Ken were water flow, depth, temperature, turbidity, Total Dissolved Solids, conductivity and land uses. Comparable results are known from investigations on assemblage of other rivers as well (Copp et al 1994;Garner 1996;Sarkar and Bain 2007;Fischer and Paukert 2008;Tongnunui et al 2009;Wu et al 2011), where the respective authors have emphasized the importance of those environmental variables influencing the fish assemblage pattern. Fish preferences of different stream of specific depths have been discussed in literature many times (Pires et al 1999) and likewise to the speed of flow (Penczak et al 2004).…”
Section: Discussionmentioning
confidence: 85%
“…Aside from velocity and depth also the physicochemical variables like water temperature, turbidity, TDS, DO and conductivity identified as significant in structuring sites and fish assemblage in River Ken. These factors were also observed in influencing the fish communities in other tropical rivers (Sarkar and Bain 2007;Tongnunui et al 2009;Wu et al 2011). Conductivity was reported to be the most important variables in structuring fish assemblages at local spatial scales across a broad region (Tongnunui et al 2009;Rosso and Quiros 2010).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Shukor et al (2008) asserts that population growth of Rasbora fish is greatly affected by pH. Ideal water acidity value (pH) for tropical fish ranges between 6-9 (the Government Regulation of the Republic of Indonesia, 2001;Alabaster and Llyod, 1980), while pH value of >10 and pH of <4 may have fatal results to the fishes (Alabaster and Llyod, 1980;Efendi, 2003), also, if species fertility is positive/negative, it firmly relates to pH (Lakra, et al, 2010;Tongnunui, et al, 2009). Other researchers, Dodds (2002) and Effendi (2003) assert that ecosystem productivity of water is classified as low if water pH is <5.0.…”
Section: Environment Of Abiotic-aquaticmentioning
confidence: 99%
“…1 Winemiller, 1996, while natural mortality is caused by low oxygen level (Das and Pande, 1980;Welcomme, 2001). Dissolved oxygen level is boundary factor in water (Lakra, et al, 2010;Tongnunui, et al, 2009;Naughton, 1996) and deoxygenation may have fatal result to fish (Green, et al, 2009). Sulistiyarto (2013) asserts that DO level in flood plain of Rungan River, Central Kalimantan as habitat of R. argyrotaenia fish is 1.8-3.1 mg/l.…”
Section: Environment Of Abiotic-aquaticmentioning
confidence: 99%